2021
DOI: 10.1029/2021jd035446
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical Characteristics of the Coexisting Frontal and Warm‐Sector Heavy Rainfall in South China

Abstract: South China, located in the north of the South China Sea and at relatively low latitudes, is often influenced by warm and moist air from the sea, which is one of the regions where heavy rainfall frequently occurs. Several field campaigns were carried out during the past 40 years, and mainly focused on the mechanisms of the initiation and maintenance of heavy rainfall over South China (e.g., Huang, 1986;Luo et al., 2017;Zhang et al., 2011;Zhou, 2003). Findings from these field campaigns have greatly advanced ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Considering the dependence of the radar data quality on the distance from the GZRD, a ring zone of 30─85 km from the GZRD is selected as the analysis region. A quantitative retrieval algorithm of rain rate based on specific attenuation and specific differential phase ( K dp ) (Y. Wang et al., 2019) is applied to the lowest scanning angle (0.5°), and the results are gridded to a spacing of 250 m. With observations from the GZRD and six 2DVDs at the Longmen Cloud Physics Experiment Base of the Chinese Meteorological Administration (CMA) (locations are shown in Figure 1), the LWC, IWC, and RSD are estimated using the Z dp method (Carey & Rutledge, 2000; Han et al., 2021) combined with the constrained‐Gamma model (G. Zhang et al., 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the dependence of the radar data quality on the distance from the GZRD, a ring zone of 30─85 km from the GZRD is selected as the analysis region. A quantitative retrieval algorithm of rain rate based on specific attenuation and specific differential phase ( K dp ) (Y. Wang et al., 2019) is applied to the lowest scanning angle (0.5°), and the results are gridded to a spacing of 250 m. With observations from the GZRD and six 2DVDs at the Longmen Cloud Physics Experiment Base of the Chinese Meteorological Administration (CMA) (locations are shown in Figure 1), the LWC, IWC, and RSD are estimated using the Z dp method (Carey & Rutledge, 2000; Han et al., 2021) combined with the constrained‐Gamma model (G. Zhang et al., 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Applications of ground‐based dual‐polarization radar observations provide a new point of view on convective structures and precipitation microphysics in both ice and liquid phases (e.g., Bringi et al., 2003; Kumjian & Ryzhkov, 2012). The newly available observations from dual‐polarimetric radars over coastal South China have been used mostly in case studies (e.g., Han et al., 2021; M. Li et al., 2021). Yu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing analysis, the warm‐sector deep convection in Eastern China is characterized by abundant GHs, obvious KnormalDnormalP ${K}_{\mathrm{D}\mathrm{P}}$ and ZnormalDnormalR ${Z}_{\mathrm{D}\mathrm{R}}$ columns, and elevated low‐level raindrop number concentrations, similar to the monsoon convection in other regions (Chang et al., 2015; Han et al., 2021; Rowe et al., 2011). We also notice that low‐level raindrop characteristics (DSD and rainfall intensity) seem to evolve with ice‐phase microphysics (polarimetric radar signatures and GH distributions) above the freezing layer.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the YJ S-POL and the Guangzhou polarimetric radar work in the same scanning mode and at the same frequency, it may be reasonable to apply the same fitting formula to YJ S-POL [44]. Therefore, we adopted the same formulas as Liu et al [59] to retrieve the RSD.…”
Section: Retrieval Of Raindrop Size Distributionmentioning
confidence: 99%
“…Application of polarimetric radars have provided a new point of view on precipitation microphysics in both ice and liquid phases [39][40][41][42]. The recent dual polarization upgrade of the operational weather radars in coastal South China has provided an opportunity to analyze the microphysical characteristics of precipitation over the coastal areas of South China, such as the rainband of Typhoon Nida [43], two consecutive mesoscale convective systems (MCSs) leading to a maximal rainfall accumulation of 451 mm on 11 May 2014 [29], the record-breaking rainfall event of 7 May 2017 influencing the megacity of Guangzhou [37], and an early summer event with coexisting frontal and warm-sector heavy rainfall [44]. Two case studies [29,37] and a statistical analysis focusing on extreme precipitation over coastal South China [45] consistently suggested that the extreme precipitation could be accompanied by a variety of convective intensities (i.e., the strength of mixed-phase processes) ranging from weak to intense, and has much more populous raindrops than the "continental" regime with a mean size larger than the "maritime" regime.…”
Section: Introductionmentioning
confidence: 99%